Pelaksanaan Penilaian Portofolio Di Sekolah Dasar - Eko Kuntarto; Rahani Gustina (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2019)
This portfolio assessment has been widely applied in primary schools in Indonesia. In practice portfolio assessment has been widely used for the teacher certification process. This study aims to describe the implementation of portfolio assessment and describe the results of the implementation of portfolio assessment in elementary schools. The approach in this study uses a qualitative approach. While the type of research used in this study is the basic theory. This research was carried out at Muara Bulian 80 / I Elementary School, Batang Hari Regency, Jambi Province. Data collection techniques used are non-participant observation, interviews, and documentation. Researchers use the Miles and Hubermen model to analyze existing data. The model is to carry out the stages that begin with collecting data, reducing, displaying data, and verifying or drawing final conclusions. This research was conducted in the even semester of the Academic Year 2017/2018. From the results of the study concluded that portfolio assessment which includes content, assessment criteria and forms of presentation of student portfolios developed by teachers include, daily tests, book reading reports, self-assessment sheets, inter-theme assessment sheets, and for class 1 also included books homework, practice books, dictation assignments and coloring